Exploring Critical Youth Media Practice: Connections and Contributions for Social Work. - Johnston-Goodstar, Katie; Richards-Schuster, Katie; Sethi, Jenna K. (Social Work, 2014)
Youth media is emerging as an interdisciplinary field of practice and subject of study. Over the last two decades, there have been many efforts within communities to engage in media, especially within the fields of youth work and education. Despite the increase in practice, we found surprisingly little attention to the potential for youth media within the social work literature. Drawing on a qualitative content analysis of program descriptions from 49 youth media groups, the authors attempt to examine the current field of youth media. Using a critical media literacy framework, the authors analyze the practice of these youth media groups and apply those findings to social work practice, education, and research.